Uncertainty Tolerance and Information Overload in High-Risk Epidemic Areas: The Mediating Role of Sense of Control - Wang, Wei (International Journal of Social Sciences and Public Administration, 2024)
The rapid advancement of information technology has led to a notable rise in information overload, a critical factor impacting the mental well-being of individuals in modern society. This is particularly pronounced in high-risk epidemic zones, where individuals are inundated with a barrage of epidemic-related information. This study aims to investigate the influence of individuals' tolerance for uncertainty on information overload in these high-risk areas, while also examining the intermediary role played by the sense of control. Through a questionnaire survey involving 250 residents of Hubei Province, the data was analyzed using SPSS and PROCESS plug-ins. The findings reveal a significant negative correlation between uncertainty tolerance and information overload, with the sense of control acting as a statistically significant mediator between the two. This underscores the potential of enhancing individuals' uncertainty tolerance and sense of control in alleviating information overload. These insights offer novel perspectives on understanding the psychological mechanisms of information processing in epidemic-prone regions and provide valuable suggestions for optimizing information dissemination strategies by bolstering individuals' psychological resilience.